2019
DOI: 10.1017/s0014479719000073
|View full text |Cite
|
Sign up to set email alerts
|

Transplanting improves the allometry and fiber quality of Bt cotton in cotton–wheat cropping system

Abstract: In cotton–wheat cropping system of Pakistan, wheat (Triticum aestivum L.) is harvested in late April; however, the optimum sowing time of Bt cotton is mid-March. This indicates a time difference of 4–6 weeks between the harvest of wheat and cotton sowing. It is hypothesized that this overlapping period may be managed by transplanting cotton seedlings (30–45 days old) in late April, after the harvest of wheat due to better performance of already established seedlings. To this end, this study was conducted to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Gangadhar et al (2018) also found a signi cantly higher oil yield and oil content of sa ower in a sa ower-linseed intercropping system in a suitable row proportion. The relay intercropping of Bt cotton in wheat could improve the growth and bre quality of Bt cotton (Shah et al 2019). Combining these results with the improvement of the survival rate of P. notoginseng in the intercropping system mentioned previously, we therefore concluded that P. notoginseng-pine tree intercropping promotes interspeci c facilitation, which can improve the growth and quality of P. notoginseng.…”
Section: P Notoginseng-pine Tree Intercropping Can Improve the Growth...supporting
confidence: 73%
“…Gangadhar et al (2018) also found a signi cantly higher oil yield and oil content of sa ower in a sa ower-linseed intercropping system in a suitable row proportion. The relay intercropping of Bt cotton in wheat could improve the growth and bre quality of Bt cotton (Shah et al 2019). Combining these results with the improvement of the survival rate of P. notoginseng in the intercropping system mentioned previously, we therefore concluded that P. notoginseng-pine tree intercropping promotes interspeci c facilitation, which can improve the growth and quality of P. notoginseng.…”
Section: P Notoginseng-pine Tree Intercropping Can Improve the Growth...supporting
confidence: 73%
“…The productivity of wheat crop is severely affected by various biotic and abiotic stresses [5,[9][10][11]. Introduction of transgenic cotton in Pakistan has aggravated the situation as the long growth period of cotton overlaps with sowing and harvesting of wheat crop [12][13][14]. Nonavailability of early maturing [3], drought-tolerant and high-yielding genotypes [5,6], low soil fertility [15], and low moisture availability [16,17] are the major reasons of low wheat production in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, in 2002, Bt cotton was introduced in India as a means of combating bollworm infestation [ 16 ]. Its technological advantage was also realized in Pakistan [ [17] , [18] , [19] , [20] ]. Cotton farmers of these countries readily accepted Bt varieties for its several benefits.…”
Section: Introductionmentioning
confidence: 99%